Halite Precipitation From Double‐Diffusive Salt Fingers in the Dead Sea: Numerical Simulations. Issue 5 (24th May 2019) - Ouillon, Raphael; Lensky, Nadav G.; Lyakhovsky, Vladimir; Arnon, Ali; Meiburg, Eckart
Abstract: We employ direct numerical simulations in order to analyze the role of double‐diffusive salt fingering in halite precipitation from hypersaline lakes. Guided by field observations from the Dead Sea, which represents the only modern deep stratified lake that precipitates halite under hydrological crisis, we consider a saturated layer of warm, salty brine (epilimnion) overlying a layer of colder, less salty brine (hypolimnion) that is also saturated. The double‐diffusive instability originating in the metalimnion gives rise to an asymmetrical pattern of less salty ascending fingers, accompanied by descending salt fingers that lose heat as they propagate through the metalimnion. The net result is a strong, downward salinity flux that leads to the undersaturation of the epilimnion, while the hypolimnion becomes oversaturated and precipitates halite. These interfacial processes within deep, hypersaline water columns in warm and dry regions suggest a potential route toward the formation of thick halite layers found in the geological record. Key Points: Guided by Dead Sea observations, we simulate double‐diffusive salt fingering in saturated, hypersaline water columns Salt fingering results in the undersaturation of the epilimnion, as well as halite precipitation in the hypolimnion The observed interfacial processes suggest a route toward the formation of thick halite layers found in the geological record